2009
DOI: 10.1309/ajcpmg37mxkypube
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of γδ T Cells in Panniculitis by Paraffin Immunohistochemical Analysis

Abstract: Cutaneous T-cell lymphomas with panniculitis-like histologic features have different clinical courses depending on whether they are composed of alphabeta T cells or gammadelta T cells, necessitating their distinction for proper prognostication. However, unlike alphabeta T cells, gammadelta T cells cannot be reliably detected in formalin-fixed, paraffin-embedded sections. We demonstrated that a commercially available antibody can detect gammadelta T cells and examined 2 cases of flow cytometry-proven gammadelta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 18 publications
3
40
0
Order By: Relevance
“…A study using the same antibody (TCR gamma+delta antibody clone 5A6.E9) can successfully recognize γδ-T-cells with membranous staining in formalin-fixed paraffin-embedded tissue, 22 but there was another one reporting that the antibody was not so robust. 23 Although membranous positive-staining of γδ-TCR is acceptable as positive, we need further study for γδ-TCR.…”
Section: Discussionmentioning
confidence: 98%
“…A study using the same antibody (TCR gamma+delta antibody clone 5A6.E9) can successfully recognize γδ-T-cells with membranous staining in formalin-fixed paraffin-embedded tissue, 22 but there was another one reporting that the antibody was not so robust. 23 Although membranous positive-staining of γδ-TCR is acceptable as positive, we need further study for γδ-TCR.…”
Section: Discussionmentioning
confidence: 98%
“…Formalin-fixed and paraffin-embedded segments were subjected to immunohistochemical analysis, as previously described [25]. The sections were deparaffinized and rehydrated.…”
Section: Methodsmentioning
confidence: 99%
“…7 Using this antibody, 2 groups have recently conducted studies on a large series of cutaneous T-cell lymphoma (CTCL) and concluded that the expression TCRg is not exclusive to CGD-TCL because TCRg was also identified in rare cases of other CTCL such as mycosis fungoides (MF) and lymphomatoid papulosis (LyP). 8,9 We present 2 cases of primary CTCL with expression of TCRg, but an indolent course supporting the suggestion that CTCL with a g/d+ phenotype may represent a prognostically heterogeneous group and may clinically and histologically overlap with MF.…”
Section: Introductionmentioning
confidence: 99%